2020
DOI: 10.1111/jace.17313
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of light weight boron‐mullite Al5BO9

Abstract: Al5BO9 is a promising thermal sealing material for hypersonic vehicles due to its low density, theoretically predicted low shear modulus, and low thermal conductivity. However, experimental investigations on the mechanical and thermal properties of bulk Al5BO9 have not been carried out. Herein, we report the mechanical and thermal properties of bulk Al5BO9 prepared by spark plasma sintering of solid‐state reaction synthesized Al5BO9 powders. The bulk (B), shear (G), and Young's (E) moduli are 148 GPa, 85 GPa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…27 Experimentally, phase pure Al 5 BO 9 powders were synthesized by solid-state reaction, 30,31 molten salt, 24 sol-gel methods, 32 and bulk Al 5 BO 9 was successfully sintered through spark plasma sintering (SPS). 26 Al 5 BO 9 has been proven to have comparable flexural strength (277 ± 35 MPa), compressive strength (814 ± 75 MPa), and fracture toughness (2.4 ± .3 MPa) to mullite. In addition, low Pugh's ratio G/B (.574) indicates its intrinsic damage tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…27 Experimentally, phase pure Al 5 BO 9 powders were synthesized by solid-state reaction, 30,31 molten salt, 24 sol-gel methods, 32 and bulk Al 5 BO 9 was successfully sintered through spark plasma sintering (SPS). 26 Al 5 BO 9 has been proven to have comparable flexural strength (277 ± 35 MPa), compressive strength (814 ± 75 MPa), and fracture toughness (2.4 ± .3 MPa) to mullite. In addition, low Pugh's ratio G/B (.574) indicates its intrinsic damage tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…15,22 Boron-mullite Al 5 BO 9 possesses a unique combination of wide band gap, low density, low thermal conductivity and high strength, which is prospective as ceramic wafer seal structure and porous high-temperature wavetransparent material of hypersonic vehicles. [23][24][25][26][27][28][29] Previous work of Zhou and Xiang 25 predicted that Al 5 BO 9 had a low theoretical density of 2.94 g/cm 3 , and its theoretical thermal conductivity declined with temperature following κ = 2404.78/T. The absorption spectrum study showed that Al 5 BO 9 could transmit electromagnetic waves, making it potential as a wave-transparent material.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations